The legacies of totalitarianism : a theoretical framework - Tucker, Aviezer 1965- (Cambridge University Press, 2015)
"The first political theory of post-Communism examines its implications for understanding liberty, rights, transitional justice, property rights, privatization, rule of law, centrally planned public institutions, and the legacies of totalitarian thought in language and discourse. The transition to post-totalitarianism was the spontaneous adjustment of the rights of the late-totalitarian elite to its interest. Post-totalitarian governments faced severe scarcity in the supply of justice. Rough justice punished the perpetrators and compensated their victims. Historical theories of property rights became radical, and consequentialist theories, conservative. Totalitarianism in Europe disintegrated but did not end. The legacies of totalitarianism in higher education met New Public Management, totalitarian central planning under a new label. Totalitarianism divorced language from reality through the use of dialectics that identified opposites and the use of logical fallacies to argue for ideological conclusions. This book illustrates these legacies in the writings of Habermas, Derrida about democracy, personal responsibility, dissidence, and totalitarianism"--